Wood species of the Central African republic - Torelli, Niko (Zbornik gozdarstva in lesarstva, 2003)
Data on ash and silica content of 28 Central African hardwoods and one monocotyledon (Dracaena mannii) are presented. Ash content varied considerably. Most of the values were in the range 0.3 - 1.4 %. The highest value was noted for Desplatsia floribunda (4.54 %) and the lowest for Pachyleasma tessmannii (0.07 %). In most species, silica was present only in trace amounts (less than 0.01 %). More than 0.1 % silica was found only in theGambea beguei (0.128 %) and Manilkara fouilloyana (0.138 %).
Keywords: les; lesne vrste; pepel; silikati; Srednja Afrika